THE DETERMINANTS OF INFLATION RATE IN INDONESIA - Setiartiti, Lilies; Hapsari, Yuni (Jurnal Ekonomi & Studi Pembangunan, 2019)
This study is try to analyzed the influence of some independent variables which believed has impact towards inflation in Indonesia, which also as one of the variables that is watched by the central bank (Bank Indonesia) as a variable that could influence inflation stability in Indonesia based on its volatility.  Those independent variables are, money supply, exchange rate, and BI rate as the interest rate, and gross domestic product.  This study used an Error correction model (ECM) to get the equilibrium model and find out the influence of every independent variables on the short-run and long-run. Overall, this research summarize the findings that has been conducted and offers some recommendation that could be taken to improve and strengthen the model’s estimation and also hoping that the model’s estimation become more relevant for the future implementation.